SAPAYUANG MARRIAGE IN MINANGKABAU FROM THE PRESPECTIVES OF MASHLAHAH, ‘URF, AND HUMAN RIGHTS - Maulana, Ramza Fatria; Kania, Dede; Kusmayanti, Hazar (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2024)
This research aimed to analyze the punishment of Sapayuang marriage according to Mashlahah perspective, ‘urf, and Human Rights correlated with the custom philosophy, Adat Basandi Syarak, Syarak Basandi kitabullah (Custom based on Islam, Islam based on Al-Qur’an) which is life foundation of Minangkabau people, the offender of sapayuang marriage accepts severe punishment. This research utilized the empirical juridical method wherein qualitative research was used as the research approach. Primary data was derived from the interview and field findings. Then, these data were analyzed using the relevant theories correlated with this issue such as classic books, books, journals, articles, law dictionaries, encyclopedia, and the previous correlated research to obtain a conclusion. There are several findings of this research, 1) the witness of sapayuang marriage is classified into mashlahah dharuriyah because maintaining the self-respect and prestige is included in mashlahah dharuriyah. If it is viewed from the perspective whether mashalahah changed or not, the prohibition of sapayuang marriage is categorized into mashlahah mutaqaiyyirah. If it is reviewed from the mashlahah side, it is characterized into mashlahah mursalah, because there is no nash which bann it. However, there is no nash which supports it. As a result, it cannot be classified into mashlahah mulghah, 2) If it is reviewed from the ‘urf object perspectives, the prohibition and punishment of sapayuang marriage are included in ‘urf amali, which means the society habits related to actions. Then, if it is seen from the scope, this prohibition is included in ‘urf  khashah which means the habit which is particularly obeyed by the people in certain region. If it is reviewed from the validity of ‘urf related to the punishment of sapayuang marriage, it is ‘urf shahih, and 3) according to the Western human rights perspective, the punishment dibuang dari nagari (expelled) and excommunicated is included in Human Right violation. It is different from the concept of Eastern human rights which emphasizes human rights as part of Islamic teaching implementation.